Exploring the impacts of biofuel expansion on land use change and food security based on a land explicit CGE model: A case study of China. (15th February 2019) - Weng, Yuwei; Chang, Shiyan; Cai, Wenjia; Wang, Can
Graphical abstract: Based on a computable general equilibrium (CGE) model augmented with an explicit land allocation module (a), land use changes induced by China's bioethanol expansion are quantified. The simulation results of different land conversion scenarios (b) indicate that planting non-grain feedstocks on newly reclaimed marginal land could increase non-grain feedstocks by 10% and save 0.217% of croplands with no deforestation by 2020 (c). Highlights: Built a general equilibrium model incorporating an explicit land use module. Different patterns of land use management were considered. Quantified land use changes among alternatives induced by bioethanol expansion. Planting energy crops on marginal land could alleviate cropland occupation. Abstract: Biofuel plays an important role in the transition to low-carbon energy systems. However, the large-scale expansion of biofuels may cause drastic land use change (LUC) due to feedstock cultivation and further result in other sustainability impacts (e.g., food supply), which are the key concerns for policy makers when designing bioenergy policies. However, biophysical models omit the indirect LUC from interactions of economic agents, whereas economic models lack the depiction of heterogeneous land use types. Thus, through either technique, it has formidable challenges to simulate land conversions among alternative uses driven by socioeconomic activities, especially policy mandates. To bridge the gap between these models by simultaneously considering land heterogeneity and market mechanisms and to gain better insights into specific national/regional cases to supplement previous global biofuel and LUC analyses, in this study, we develop a national computable general equilibrium (CGE) model augmented with an explicit land allocation module and design a scenario approach to simulate different patterns of land use management. Food grains and dedicated energy crops are considered feedstock sources and marginal land is incorporated as a potential land supply. Using this model, the case study of China quantifies the direct and indirect LUC driven by the bioethanol (one of the main biofuels) expansion of the new nationwide E10 mandate (gasoline containing 10% ethanol) in 2020, as well as the further impacts on food security. The results show that a slight land reallocation occurs with decreases in the land supply for rice (−0.016%), other non-feedstock grains and crops, as well as forest and grassland (−0.023%). The land competition among existing croplands would be intense in the non-deforestation scenario. If marginal land is reclaimed for feedstock cultivation, the cropland competition could be softened. The results of sensitivity analysis indicate that the total LUC scale would be 4.0–5.9% with no corn stockpile serving as feedstock. Additionally, the bioethanol expansion would trigger higher food prices (around +0.1%). To alleviate the negative impacts on land resources and food security, planting energy crops on marginal land could increase non-grain feedstocks by 10% and save 0.217% of croplands; therefore, it may be one of the promising pathways for sustainable biofuel development in China. This study can lay a common foundation for further integrated impact assessments of biofuel expansion.